Community Structure and Activity Dynamics of Nitrifying Bacteria in a Phosphate-Removing Biofilm - Gieseke, Armin (American Society for Microbiology, 2001)
The microbial community structure and activity dynamics of a phosphate-removing biofilm from a sequencing batch biofilm reactor were investigated with special focus on the nitrifying community. O(2), NO(2)(−), and NO(3)(−) profiles in the biofilm were measured with microsensors at various times during the nonaerated-aerated reactor cycle. In the aeration period, nitrification was oxygen limited and restricted to the first 200 μm at the biofilm surface. Additionally, a delayed onset of nitrification after the start of the aeration was observed. Nitrate accumulating in the biofilm in this period was denitrified during the nonaeration period of the next reactor cycle. Fluorescence in situ hybridization (FISH) revealed three distinct ammonia-oxidizing populations, related to the Nitrosomonas europaea, Nitrosomonas oligotropha, and Nitrosomonas communis lineages. This was confirmed by analysis of the genes coding for 16S rRNA and for ammonia monooxygenase (amoA). Based upon these results, a new 16S rRNA-targeted oligonucleotide probe specific for the Nitrosomonas oligotropha lineage was designed. FISH analysis revealed that the first 100 μm at the biofilm surface was dominated by members of the N. europaea and the N. oligotropha lineages, with a minor fraction related to N. communis. In deeper biofilm layers, exclusively members of the N. oligotropha lineage were found. This separation in space and a potential separation of activities in time are suggested as mechanisms that allow coexistence of the different ammonia-oxidizing populations. Nitrite-oxidizing bacteria belonged exclusively to the genus Nitrospira and could be assigned to a 16S rRNA sequence cluster also found in other sequencing batch systems.